EVALUATION OF PHENOTYPIC STABILITY IN BREAD WHEAT ACCESSIONS USING PARAMETRIC AND NON-PARAMETRIC METHODS - A. Yaghotipoor; E. Farshadfar; M. Saeidi (Journal of Animal and Plant Sciences, 2017)
In order to compare parametric and nonparametric stability measures, and to identify high-yield and stable bread wheat genotypes, 20 accessions were grown in a randomized complete block design with 3 replications under 6 irrigated and dryland conditions. Combined analysis of variance (ANOVA) and Bredenkamp test indicated the presence of significant genotype ×environment interactions. Parametric and non- parametric stability statistics introduced genotypes: G13, G15 and G18 as the most stable. The statistics , bi, and were desirable for the simultaneous selection of yield and stability. Spearman's rank correlation indicated that most non-parametric measures were significantly (P<0.01) inter-correlated with parametric measures and therefore can be used as alternatives.
Keywords: Bread wheat; GE interaction; parametric and non-parametric measures; stability